Model pengembangan keterampilan menulis artikel dan manajemen tatakelola penerbitan jurnal ilmiah bagi organisasi profesi guru - Muhammad Saleh; Sultan Sultan (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
The implementation of this Community Serviceprogram was driven by the findings of the field which showedthe low competence of teachers in conducting publications inscientific journals. This Community Service program aims toincrease partner knowledge and skills in writing scientificarticles and managing scientific journals. Two partner groupsinvolved in this program, namely: (1) Indonesian TeachersAssociation of Maros Regency; and (2) Makassar CityIndonesian Teachers Association. The model of developingwriting skills and governance of scientific journals offeredconsists of four stages, namely: (1) workshops to improvescientific article writing skills; (2) training to improve partnerknowledge and skills in the management of scientific journalmanagement; (3) guided and sustained writing practice; and(4) mentoring management and publishing scientific journals.